Polygalasaponin XXXII from Polygala tenuifolia root improves hippocampal-dependent learning and memory - Xue, Wei (Nature Publishing Group, 2009)
AIM: The aim of this study was to investigate the cognition-enhancing activity and underlying mechanisms of a triterpenoid saponin (polygalasaponin XXXII, PGS32) isolated from the roots of Polygala tenuifolia Willd. METHODS: The Morris water maze was used to evaluate the spatial learning and memory of mice. To detect the basic properties of synaptic transmission and long-term potentiation (LTP) in the dentate gyrus of rats, electrophysiological recordings were made of evoked potentials. Western blotting analysis and immunofluorescence assays were used to determine the phosphorylation of extracellular signal-regulated kinase (ERK), cAMP response element-binding protein (CREB), synapsin I and the expression of brain derived neurotrophic factor (BDNF). RESULTS: When administered at 0.125, 0.5, or 2 mg/kg, PGS32 could significantly prevent scopolamine-induced cognitive impairments in mice. Intracerebroventricular (icv) administration of PGS32 greatly enhanced basic synaptic transmission in the dentate gyrus of rats and induced LTP. In primary hippocampal neurons, as well as in the hippocampus of maze-trained mice, PGS32 activated the mitogen-activated protein (MAP) kinase cascade by promoting phosphorylation of ERK, CREB and synapsin I. The expression of BDNF was also greatly enhanced in the hippocampus. CONCLUSION: Our findings suggest that PGS32 can improve hippocampus-dependent learning and memory, possibly through improvement of synaptic transmission, activation of the MAP kinase cascade and enhancement of the level of BDNF. Therefore, PGS32 shows promise as a potential cognition-enhancing therapeutic drug.